Analysis of School Life Expectancy Prediction in North Sumatra using the ARIMA Method for the 2024-2025 Period - Sudewo, Egi Dio Bagus; Biddinika, Muhammad Kunta; Dahlan, Khoirul Anam; Prayitno, Kintung; Kariyamin, Kariyamin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This study analyzes the projection of the School Life Expectancy (HLS) in 33 districts/cities in North Sumatra Province using the ARIMA method. Historical HLS data from 2019 to 2023 were used to forecast the HLS values for 2024 and 2025. The prediction results show an increase in HLS in most regions, with several districts/cities such as Labuhan Batu, Pematangsiantar City, and Padangsidempuan City experiencing significant growth. However, some regions like Mandailing Natal and Samosir show a more stable trend without significant increases. These findings indicate disparities in access and quality of education across various regions in North Sumatra. Overall, the ARIMA model provides a positive forecast for future HLS improvements, though regional disparities require special attention from relevant authorities to promote equal access to education.